Gender Equality and Work-Life Balance Glass Handcuffs and Working Men in the U.S. - Blithe, Sarah (2018)
Pressure to achieve work-life "balance" has recently become a significant part of the cultural fabric of working life in United States. A very few privileged employees tout their ability to find balance between their careers and the rest of their lives, but most employees face considerable organizational and economic constraints which hamper their ability to maintain a reasonable ""balance"" between paid work and other life aspects-and it is not only women who struggle. Increasingly men find it difficult to ""do it all."" Women have long noted the near impossibility of balancing multiple roles, but it is only recently that men have been encouraged to see themselves beyond their breadwinner selves. Gender Equality and Work-Life Balance describes the work-life practices of men in the United States. The purpose is to increase gender equality at work for all employees. With a focus on leave policy inequalities, this book argues that men experience a phenomenon called ""the glass handcuffs,"" which prevents them from leaving work to participate fully in their families, homes, and other life events, highlighting the cultural, institutional, organizational, and occupational conditions which make gender equality in work-life policy usage difficult. This social justice book ultimately draws conclusions about how to minimize inequalities at work. Gender Equality and Work-Life Balance is unique as it laces together some theoretical concepts which have little previous association, including entrepreneurialism; leave policy, occupational identity, and the economic necessities of families. This book will therefore be of particular interest to researches and academics alike in the disciplines of Gender studies, Human Resource Management, Employment Relations, Sociology and Cultural Studies.